ANALISIS KEPUTUSAN PEMBELIAN MELALUI BRAND POSITIONING YANG DIPENGARUHI OLEH CELEBRITY ENDORSER: Studi Pada Situs Belanja Online Fashion Muslim Lokal Hijup.com - Firda Ariani, - (2019)
This research is a quantitative research that aims to determine the effect celebrity endorser, and brand positioning to purchase decision. Population in this research is citizen of Pekayon Sub-district, Jakarta Timur. The sample size was taken by 50 respondents, with non probability sampling method, especially purposive sampling. Data collection was done through questionnaires. Analytical technique used is the method of analysis PLS (Partial Least Square). The results of this study show that (1) celebrity endorser has a significant influence on Brand Positioning with coefficient value of the path of 0,838. (2) celebrity endorser has a no significant effect on Purchase decision with coefficient value of 0,042. (3) brand positioning has a significant effect on Purchase Decision with coefficient value of 0,796. (4) Celebrity endorser through Brand Positioning has a significant effect on Purchase Decision with coefficient value of 0,667.